Average pubertal timing, characteristics and menstrual patterns of Nigerian girls: Implication for sex education - Faith C Diorgu; Kelechim N Diorgu (Journal of Gynecological Research and Obstetrics - Peertechz Publications, 2020)
Introduction: Age at menarche reflects the beginning of sexual maturation and is affected by nutritional status and prevailing environmental conditions. This study examined the age at menarche, breast and pubic hair development of girls in Southern Nigeria and explored their menstrual pattern Method: A cross-sectional descriptive study design was adopted, with structured questionnaire. Descriptive statistics was used to analyze data collected from 648 randomly selected girls in high school. Analysis was supported with SPSS software package. Results: The average age of menarche was reported as 12.8 ± 1.6 years (ranging from 9 to 19). Twenty seven percent (27%) of the girls had their menarche before age 12 and 61% had their menarche between 12 and 14 years, while (12%) had menarche at age 15 to 16 years. The lowest age at menarche was 9 years with the highest being 16 years. The modal menarcheal age was 13. At age 10 to 12 years only (16%) respectively had developed breast and pubic hair. Majority of the respondents with breast (55%) and pubic hair (55%) were between ages 13 and 15 years. Conclusion: The age at menarche and other menstrual patterns observed in this study are similar to adolescent pubertal timing and menstrual characteristics described by studies.